Todo dia é dia de feira: um estudo sobre as feiras da cidade de Santa Maria - RS - Ibdaiwi, Thiago Kader Rajeh (2023)
Free fairs are not just a conglomerate of marketers with the purpose of selling. Through a more scientific approach to their organization, one notices a complex organization, of peculiar dynamic depending on the occupied urban space. Movements, affection, and goods-and services exchanges are elements that are a part of each fair. Internal and subjective from each geographical space occupied, created from sharing life experiences and food amongst those who maintain its functioning. However, beyond organizational processes, free fairs are comprised of human beings, of specific characteristics, whether individual or collective, of subjects conditioned to sentiments, that is, of human being who also seek quality of life. Furthermore, free fairs are maintained by men and women who are marked by their social, rural, and urban contexts, playing the role of agriculture workers. Therefore, the research problem emerges from the following questions: what are the conceptions and work conditions that free fairs present in Santa Maria/RS? Is there equality and equity between women and men when one talks about free fairs? Which facts may explain the quality of life of Family agriculture works that act as marketers in free fairs? Which domains of quality of life prevail among marketers? In order to provide answers to the questions, the main objectives of this research are: i) to analyze the quality of life of family agriculture workers that act on free fair in Santa Maria; ii) to verify if there is equity between man and women that work as marketers; iii) to verify and describe the work condition perceptions in according to the perspective of marketers and which life quality domains prevails among the agents of this study. From the main objectives, specific objectives arise: i) to collect data about the prevailing profile of agriculture workers who participate in free fair in Santa Maria/RS; ii) to verify the rural female context and if there is equity between men and women; iii) to identify work conditions and how they interfere within the work of free fair marketers; iv) to identify which physical and psychological domains are more compromised from what was presented by marketers in relation to their quality of life. To answer the research problem from the general and specific objectives, a qualiquantitative methodology was chosen: quantitative because of the numeric character about conditions and perceptions of free fair marketers upon their work conditions and quality of life, through an interview script composed of single choice and multiple-choice questions. The qualitative nature of research functions to interpret the answers provided by the agents of the research, using WHO’s instrument – WHOQOL-BREF – in which approaches domains that serve this research. 90 marketers were the agents of this study who work in many free fairs in Santa Maria – RS. The results approach more than just aspects related to quality of life, the results intertwine stories of life that show the overcoming of agriculture workers that seek, through free fairs, a way of commercialization their products. Family groups of small agriculture workers that sell their products, that share their stories and wisdom, inherited from older generations, provide more than food, they exchange knowledge. Despite the difficulties, free fair marketers classify their quality-of-life aspects as positive, being the main interference factor the work conditions and the lack of conditions within the workplace. However, factors as Family groups, religion and satisfaction with the professions are constant questions among free fair marketers.